Formulation and evaluation of Chinese eucalyptus oil gel by using different gelling agents as an antimicrobial agent - Deepshikha Dubey; Vibha; Yogesh Murti; Pranay Wal; Akash Ved; Parshant Kumar; Anuj Kumar Sharma; Harinath Dwivedi; Anita Singh; Manjul Pratap Singh; Mayank Kulshreshtha (Pharmacological Research - Modern Chinese Medicine, 2023)
Background: The aim of the present study was to formulate and evaluate the herbal gels containing Chinese Eucalyptus Oil or Eucalyptus globulus Labill. (E. globulus) using different polymers (Methylcellulose, HPMC, Carbopol-940) and checked their antimicrobial effects against different microorganisms. the oil from Eucalyptus globulus has a good medicinal value in the Chinese medicine system. Methods: A topical gels formulation were designed by using mentioned oil with polymers, as well as gelling agent with different excipients. Microbial species, such as Staphylococcus aureus (S. aureus), Bacillus subtilis (B. subtilis), Escherichia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa), Aspergillus tubingensis (A. tubingensis) have been selected for the study. Results: The gel's physical properties complied with the necessary standards. These four gel compositions efficiently stop some strains' development. Studies show that the gel was also particularly effective against gram-negative and fungal bacteria. The Zones of inhibition (ZOI) were found between 1.2 and 10.2 µm. The formulation F4 have good antifungal potential. Conclusion: The herbal gel was found to have highly promising anti-fungal and anti-fungal activity against many skin-related infections in a concentration-dependant manner but further research must be needed.